Menelisik Ruang Lingkup dan Pentingnya Ilmu Hukum Perdata dalam Kehidupan Bermasyarakat - Dalila, Bella; Andrian, Sri; Munawir (Al-Mizan, 2024)
Civil law is a branch of legal science with a broad scope and significant relevance in societal life. It not only governs private rights but also provides clear guidelines on individual obligations in social relationships. This study aims to analyze the scope of civil law and explore its relevance in maintaining harmony and justice in the modern era. Using literature study methods and a descriptive-analytical approach, this research examines various aspects of civil law, from agreements to rights protection in the digital era. The results indicate that civil law has the flexibility to adapt to contemporary developments, such as electronic transactions and data protection regulations. However, gaps were identified in public understanding of civil law applications, especially in resolving complex conflicts involving multiple parties. This study highlights the importance of education and civil law dissemination as strategic steps to enhance public understanding and accessibility to this legal mechanism. Consequently, civil law can function more optimally as an instrument of justice and empowerment amidst social dynamics.